2020
DOI: 10.3389/fpsyt.2020.00003
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness Measurements in Children With Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is the most commonly diagnosed neurodevelopmental disorder in childhood. It is a heterogeneous disorder in terms of clinical presentation that is probably due to the frequent occurrence of comorbidity. Children with ADHD more frequently report sleep disorders (notably delayed sleep phase syndrome) and excessive daytime sleepiness (EDS) than typically developing children. The aim of this article is to propose a narrative review of the assessment of EDS in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The model provides an explanation for the attentional deficits, especially related to sustained attention and vigilance, and for the ADHD subtypes (Hegerl and Hensch, 2014). Furthermore, sleep problems and circadian alterations are very common in ADHD patients, and many studies (e.g., Yoon et al, 2012;Bioulac et al, 2020) have indicated that all factors inducing sleep deficits and dysregulation of arousal can impair ADHD symptoms. Finally, drug stimulants are known to reduce slow wave activity, attention deficits, and hyperactivity through the regularization of the arousal level.…”
Section: Resultsmentioning
confidence: 99%
“…The model provides an explanation for the attentional deficits, especially related to sustained attention and vigilance, and for the ADHD subtypes (Hegerl and Hensch, 2014). Furthermore, sleep problems and circadian alterations are very common in ADHD patients, and many studies (e.g., Yoon et al, 2012;Bioulac et al, 2020) have indicated that all factors inducing sleep deficits and dysregulation of arousal can impair ADHD symptoms. Finally, drug stimulants are known to reduce slow wave activity, attention deficits, and hyperactivity through the regularization of the arousal level.…”
Section: Resultsmentioning
confidence: 99%
“…An objective way to measure excessive sleepiness during the day is useful as previous studies have pointed to an increase of sleep disorders in adolescents, where a sleep phase delay is characteristic and this symptom could indicate a shorter sleep duration or unfavorable sleep quality. In children and adolescents, it might be associated, as consequences, with learning and behavioral problems and attention disorders [10][11][12][18][19][20] . Further, sleepiness can also be a pathway linking race and socioeconomic status with worse academic and cognitive outcomes in middle childhood 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of narcolepsy and ADHD overlap (Oosterloo et al 2006; Bioulac et al 2020), Bioulac 2020). Both pathologies respond well to DA drugs.…”
Section: Discussionmentioning
confidence: 99%